Extent of Adoption of Improved Animal Husbandry Practices by Dairy Farmers of Morar Block in Gwalior District (Indian Journal of Extension Education, 2017)
The present study was conducted to assess the extent of adoption of improved animal husbandry practices by dairy farmers of Morar Block in Gwalior district of Madhya Pradesh. Simple random sampling method was used to select 120 dairy farmers as respondents. The findings revealed that reproductive practices like artificial insemination at proper time of heat, with semen of good bull was regularly adopted by majority (80.00%) of the dairy farmers, regarding nutritional practices provision of ad lib clean and fresh water was regularly adopted by 85.00 per cent of dairy farmers, thirdly, washing of hands and udder before milking was the major (96.67%) management practices regularly adopted by farmers. To control disease prompt reporting of outbreak of a contagious disease to the local veterinarian was the adopted by 76.67 per cent of the dairy farmers. Lastly, marketing practice like purchasing of animals from reliable sources after following scientific method of scoring/weightage on production was adopted by (41.67 %) the dairy farmers.